Licensing luxury fashion in transatlantic and colonial economies: beyond Paris and New York (Revista de Ensino em Artes, Moda e Design, 2024)
During the postwar era, luxury fashion firms entered a new phase of their international growth with the licensing of their brands. The French haute couture firm Dior was pioneer in licenses, and established branches in a series of countries around the world. Inspired by the transatlantic successes of firms such as Jean Dessès, Christian Dior, and Norman Hartnell, French luxury firms registered their brands internationally and replicated the registration of trademarks in numerous countries. This paper further examines the reach of luxury fashion and beauty brands in the colonies of France and of Belgium. This shows that the fashion firms expanded their transatlantic expertise, and that this created newer transatlantic circuits in return.
Keywords: trademark; luxury; transatlantic; brands; commerce